ANALISIS PENDEKATAN KEADILAN RESTORATIF TERHADAP PEREMPUAN PELAKU TINDAK PIDANA DI RUTAN SERANG - Rohayati, Ade Cici (Politeknik Pengayoman Indonesia, 2024)
Imprisonment is still an option for resolving criminal cases committed by criminal perpetrators, including female perpetrators. Imprisonment for certain cases should be carried out as an ultimum remedium by first considering providing alternative solutions through restorative justice by fulfilling a sense of justice for all parties involved through efforts to involve victims, perpetrators and the local community as well as investigators as mediators. The imposition of imprisonment, which is still dominant on criminal offenders, also has a direct impact on the increasing occupancy rate in correctional institutions compared to the available housing capacity. This research aims to determine restorative justice for female criminal perpetrators and obstacles in implementing restorative justice for women who are in conflict with the law as perpetrators with the research location at the Serang State Detention Center. The research method used is normative-empirical legal research where data will be collected using document study techniques such as statutory regulations and literature which will be analyzed descriptively qualitatively and complemented by interviews with female prisoners at the Serang State Detention Center. The research results show there are no specific arrangements for handling criminal cases using a restorative justice approach for women who commit criminal acts in the investigation and prosecution stages, and there are obstacles in implementing restorative justice for women perpetrators of criminal acts that cannot be carried out optimally due to the perpetrator's lack of knowledge of alternative solutions through restorative justice and the failure to reach an agreement between the perpetrator and the victim, and there is no agreement on fulfilling the rights of victims and the responsibilities of perpetrators